Sexual Function and Quality of Life in Adult Male Individuals with Exstrophy-Epispadias Complex-a Survey of the German CURE-Network - Traceviciute, Justina; Zwink, Nadine; Jenetzky, Ekkehart; Reutter, Heiko; Hirsch, Karin; Stein, Raimund; Roesch, Wolfgang H.; Ebert, Anne-Karoline (Urology, 2018)
To investigate sexual function and quality of life (QoL) in adult male individuals with exstrophy-epispadias complex (EEC). Data from the German Network for Congenital Urorectal Malformations (CURE-Net) were used.Fifty-one male participants (>=18 years) recruited by CURE-Net between 2009 and 2012 were re-contacted per mail and asked to fill out 4 questionnaires including International Index of Erectile Function (IIEF-5), Cologne Assessment of Erectile Dysfunction (KEED), the Short-Form 36 (SF-36), and one self-designed questionnaire about their medical history, current health status, and sexual experience. The SF-36 results were compared with general German population.Nineteen male participants (37%) completed all questionnaires (median age 26 years, 84% classical bladder exstrophy). The majority (68%) was reconstructed in a staged or single-staged approach; further 32% had a primary urinary diversion. Seventy-four percent of the participants reported a certain degree of urinary incontinence. Mean IIEF-15 results showed mild to moderate or moderate impairment in all domains. The SF-36 results revealed no difference in the German population. Subgroup analysis showed statistically significant lower results in certain SF-36 domains with regard to incontinence, dissatisfaction with genital appearance, and antihypertensive drug intake.Although there is no difference in overall QoL comparing male individuals with EEC to the general German population, incontinence, dissatisfaction with genital appearance, and taking antihypertensive medication seem to have a considerable impact on QoL. Furthermore, mild to moderate erectile dysfunction and moderate intercourse satisfaction were confirmed, suggesting the need for further improvement in care for adult male individuals with EEC.
EVALuna2:65117